O percurso da educação em Emmanuel Lévinas : a moralidade em movimento e vida - Bonamigo, Gilmar Francisco (2013)
The object of this thesis is the morality as human education itself. This writing is a course that goes along with and takes note of the course of the moral Self in the human as its education. The fundamental objective of this writing is to reveal an educative course as a path in movement and life in which every Self may come to be moral. What is the violence? What is the human? What is moral? This writing brings a long answer. What is education as morality? This writing brings a concrete answer. Is it possible an education as morality of a Self and of any Self that might face the violence and leads it to failure considering a world of revenge, of war, of the prior assertion of the Self? This writing brings an incarnated answer. How the morality went to or even could go to the entire soul of a moral Self or in its course as its education? Is there a way for this? Is there a path to the human education? Are there appropriate mediations? There goes one of the last great answers of this thesis. The writing of education as morality in movement and life brings in its course a hermeneutics of violence in an archaeology of its roots, of its movements and of the manner it happens. The writing of education as morality in movement and life brings a hermeneutics of the human according to Emmanuel Lévinas: the human in its levels of elevation is the One-for-the-Other and reveals itself as transcendence. This writing of education as morality in movement and life brings a hermeneutics of education as morality from the inside of the human. The human translated with Lévinas is revealed in the movement and life of Janusz Korczak, Mohandas K. Gandhi and Emmanuel Lévinas himself as the accomplished teleology of the gift of Self: education made of morality as the life itself. This writing reveals that the life and pedagogical work of Janusz Korczak, the life and ethical work of Emmanuel Lévinas, the life and emancipatory work of Mohandas K. Gandhi have their conditions of human possibilities. The research is eminently bibliographic and the method that puts the research and the writing in action, from the beginning to the end, is the Critical Hermeneutic of Paul Ricoeur like an open and unlimited arch of interpretation on spirals of belonging and distancing. By the end of this hermeneutic course, this writing gets to the point that the one who morally moves his life as his education followed a certain path which lived in the mediations turns the possibility of a human education and that the moment the One-for-the-Other diachronically comes to turn the movement and life of the entire soul is also the moment the violence comes to fail: the transcendence of the Goodness for the Other archaeologically crosses the Self and the teleology like the calling to the gift of Self happens in the world.